DESAIN MESIN PENGAMBIL TELUR PUYUH OTOMATIS BERBASIS IOT MENGGUNAKAN METODE QFD - Mohammad Faisal Arsad, Mohammad Faisal Arsad; Dyah Riandadari S.T.,M.T. , Dyah Riandadari S.T.,M.T.; Arya Mahendra Sakti S.T.,M.T. , Arya Mahendra Sakti S.T.,M.T.; Lailatus Sa'diyah Yuniar Arifianti S.T.,M.T., Lailatus Sa'diyah Yuniar Arifianti S.T.,M.T. (Universitas Negeri Surabaya, 2026)
This study aims to design an automatic quail egg collection machine based on the Internet of Things (IoT) using the Quality Function Deployment (QFD) method as the primary approach to translating farmers’ needs into technical machine specifications. Common problems faced by quail farmers include inefficient egg collection time, the risk of egg damage due to manual handling, and the limited availability of automatic technologies to support production processes. Therefore, an automatic machine design is needed to improve productivity, safety, and work efficiency for farmers. The QFD method was used to identify user needs through a questionnaire distributed to 30 quail farmers. The analysis resulted in nine key attributes prioritized in the design, namely cage capacity, cage material selection, frame material selection, frame thickness, roof material, price, cage dimensions, strength factors, and safety factors. These attributes were then translated into technical specifications through the House of Quality (HoQ), which established three priority technical responses: a price range of Rp 6–9 million, cage dimensions (120 × 50 × 23–18 cm), and a frame thickness of 1 mm. The final outcome of the study is an automatic quail cage design with a capacity of 40 birds, developed using Autodesk Inventor in both 2D and 3D formats. The cage structure uses galvanized wire, galvanized hollow steel frames, and a fiber roof. This design is considered capable of meeting farmers’ needs by providing a more efficient, safe, and functionally appropriate automatic egg collection system for small- to medium-scale quail farming.